Italian version of Dyspnoea-12: cultural-linguistic validation, quantitative and qualitative content validity study - Caruso, Rosario; Arrigoni, Cristina; Groppelli, Katia; Magon, Arianna; Dellafiore, Federica; Pittella, Francesco; Grugnetti, Anna Maria; Chessa, Massimo; Yorke, Janelle (Acta Biomedica Atenei Parmensis, 2018)
Background: Dyspnoea-12 is a valid and reliable scale to assess dyspneic symptom, considering its severity, physical and emotional components. However, it is not available in Italian version due to it was not yet translated and validated. For this reason, the aim of this study was to develop an Italian version Dyspnoea-12, providing a cultural and linguistic validation, supported by the quantitative and qualitative content validity. Methods: This was a methodological study, divided into two phases: phase one is related to the cultural and linguistic validation, phase two is related to test the quantitative and qualitative content validity. Linguistic validation followed a standardized translation process. Quantitative content validity was assessed computing content validity ratio (CVR) and index (I-CVIs and S-CVI) from expert panellists response. Qualitative content validity was assessed by the narrative analysis on the answers of three open-ended questions to the expert panellists, aimed to investigate the clarity and the pertinence of the Italian items. Results: The translation process found a good agreement in considering clear the items in both the six involved bilingual expert translators and among the ten voluntary involved patients. CVR, I-CVIs and S-CVI were satisfactory for all the translated items. Conclusions: This study has represented a pivotal step to use Dyspnoea-12 amongst Italian patients. Future researches are needed to deeply investigate the Italian version of  Dyspnoea-12 construct validity and its reliability, and to describe how dyspnoea components (i.e. physical and emotional) impact the life of patients with cardiorespiratory diseases.